"LA CANOPEE" in Paris—An Innovative Architecture, a Challenge for Engineering. Issue 3 (1st August 2016) - Grange, Vincent
Abstract: At the heart of Paris, "Les Halles" is both the busiest underground station in Europe, and one of the busiest underground commercial malls in France. Above this very complex structure— and constrained environment— the Canopy is an innovative glass roof structure with a surface of nearly 1 ha and without any supporting column. The architects of this project chose the name with reference to an undulating upper layer of forest cover which protects the ground from the rain. Erecting the Canopy poses three specific complexities: – the necessity to cope with the existing underground supporting structure without transferring the horizontal loads; – the complex geometry of this roof which is bent in the vertical and horizontal directions; – the location of the works, in the very centre of Paris and above a mall and a metro station, imposing very specific construction methods and safety measures.